Implementation of the ‘Merdeka Belajar–Kampus Merdeka’ Policy at Universitas Islam Negeri Syarif Hidayatullah Jakarta - Akmalia, Rizki; Siahaan, Amiruddin; Lubis, Reza Noprial (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This research seeks to find out how the implementation of independent learning on an independent campus is implemented by Syaif Hidayatullah State Islamic University Jakarta. This research uses descriptive qualitative methods with the data collection techniques used are observation, interviews and documentation, with primary data sources coming from the Vice Chancellor for Academic Affairs, Chairperson of Quality Assurance Agency, Deputy Dean for Academic Affairs Faculty of Sharia and Law and Deputy Dean for Academic Affairs Faculty of Science and Technology. Data analysis uses a flow of activities, namely reducing data, presenting data, and drawing conclusions. The study found that ‘Merdeka Belajar–Kampus Merdeka’ implementation at UIN Jakarta faces challenges in curriculum alignment and partner engagement, but also presents opportunities for enhanced student autonomy. In addition, this research can provide added value to partner institutions, especially Universitas Islam Negeri in Indonesia, by providing in-depth analyses of the best way to combine national policies with local and religious needs at Universitas Islam Negeri.